2010
DOI: 10.1002/acp.1737
|View full text |Cite
|
Sign up to set email alerts
|

Working memory in spatial knowledge acquisition: Differences in encoding processes and sense of direction

Abstract: This study examined how different components of working memory are involved in spatial knowledge acquisition for good and poor sense-of-direction (SOD) people. We employed a dual-task method, and asked participants to learn routes from videos with verbal, visual and spatial interference tasks and without any interference. Results showed that participants with a good SOD encoded landmarks and routes verbally and spatially, and integrated knowledge about them into survey knowledge with the support of all three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 27 publications
7
55
0
Order By: Relevance
“…On the basis of these results, we propose a model for the processing of egocentric and allocentric survey knowledge for people with a good and poor SOD (Figure 3), which extends the model of landmark, route, and survey knowledge acquisition proposed by Wen et al. (2011).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…On the basis of these results, we propose a model for the processing of egocentric and allocentric survey knowledge for people with a good and poor SOD (Figure 3), which extends the model of landmark, route, and survey knowledge acquisition proposed by Wen et al. (2011).…”
Section: Discussionmentioning
confidence: 75%
“…Verbal processing may help abstracting the characteristics of landmarks and routes analytically, and spatial processing may help encoding their metric or relational properties. The past finding that verbal and spatial working memory were involved in the acquisition of landmark and route knowledge (Garden et al., 2002; Meilinger et al., 2008; Wen et al., 2011) seems to reflect the fact that these two types of knowledge are basically tied to egocentric views.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, predefining an order by movement or successive object presentation might generate an additional verbal memory trace constructed along the learning order. Verbal memory was shown to be involved within route learning (Meilinger, Knauff, & Bülthoff, 2008;Wen, Ishikawa, & Sato, 2011) as well as learning of an object layout (Meilinger & Bülthoff, 2013). Memory retrieval in the subsequent placement task might be initialized following this verbal code.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Wen et al (2011Wen et al ( , 2013 examined the involvement of three different components of working memory in the acquisition of spatial knowledge in relation to the participants' sense of direction (SOD). They showed that people with a good SOD encoded landmarks and routes verbally and spatially and integrated this knowledge with the support of all three components of working memory.…”
Section: Introductionmentioning
confidence: 99%